Population-based cross-sectional analysis of cannabis use among Kentucky adults, 2020–21 - Sydney Shafer; Gunnar Kennedy; W. Jay Christian (Journal of Cannabis Research)
Abstract Purpose We conducted this study to assess cannabis use rates in the state of Kentucky relative to socioeconomic, demographic, and geographic factors, as well as reasons for use and modes of use, before the legal medical marijuana market commences in 2025. Methods We pooled Kentucky Behavioral Risk Factor Surveillance System (BRFSS) data for 2020–2021 and used weighted responses for all analyses. We estimated current cannabis use (at least once in the past 30 days), and heavy use (at least 20 of the past 30 days) prevalence rates for Appalachian, Delta, and Central geographic regions of Kentucky. We tabulated descriptive statistics and used multivariable logistic regression to identify characteristics of individuals who used cannabis. Results The prevalence of cannabis use was lower in Kentucky (10%) than nationally (about 13%). Of those who used cannabis, 42% used it daily or near daily. Those who were male, ages 18–34, never married, black, less than HS education, lower household income, and lived in the Central region were more likely to use cannabis. Among those who used cannabis, mode of use varied somewhat among age groups, education levels, income groups, and marital status, but smoking was most common—78% overall. About 33% reported using cannabis for recreation alone, 24% for medical reasons alone, and 43% for both reasons. Conclusion Despite the illegal status of cannabis in Kentucky, its use is common across population sub-groups. A large proportion of Kentuckians using cannabis do so daily or near daily, and most for a medical purpose. Smoking, however, remains the most common mode of use.